Oral Myiasis of Maxilla (Palatal Gingiva) - Vasanthakumar, Vanmathi (Contemp Clin Dent, 2020)
Myiasis is an invasion of tissues and organs of humans or animals by fly larvae. Oral myiasis is a rare pathology associated with a medical condition, poor oral hygiene, mouth breathing, and incompetent lip. We present a case of oral myiasis of the maxillary anterior region of the palate, in a 12-year-old male with cerebral palsy and poor oral hygiene. The diagnosis was made on the presence of larvae. The mechanical removal of larvae with hemostat was carried out with ivermectin oral therapy.